2019
DOI: 10.3390/pharmaceutics11040185
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Liposomal Formulations Containing Phytosterols Extracted from Canola Oil Deodorizer Distillate along with Tocopherols as Food Additives

Abstract: Phytosterols are plant sterols recommended as adjuvant therapy for hypercholesterolemia and tocopherols are well-established anti-oxidants. However, thermo-sensitivity, lipophilicity and formulation-dependent efficacy bring challenges in the development of functional foods, enriched with phytosterols and tocopherols. To address this, we developed liposomes containing brassicasterol, campesterol and β-sitosterol obtained from canola oil deodorizer distillate, along with alpha, gamma and delta tocopherol. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…Gamma and beta tocopherols are positional isomers and were not chromatographically resolved. As such, they are quantified collectively, as previously done using gamma tocopherol as reference standard [ 39 , 58 , 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gamma and beta tocopherols are positional isomers and were not chromatographically resolved. As such, they are quantified collectively, as previously done using gamma tocopherol as reference standard [ 39 , 58 , 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…The limited development to date has not been due to a lack of potential applications, but to difficulties in finding safe, low-cost ingredients and economical processing methods suitable for producing large volumes of nanoliposomes/tocosomes with batch-to-batch consistency. The recent development of Mozafari method [41,42] and pro-liposome techniques [43] offers possible solutions to many of the food processing problems. Moreover, ongoing research into the application of cost-effective commercial lecithin ingredients may lead to suitably low product costs [44].…”
Section: Applications In the Food Industrymentioning
confidence: 99%
“…Briefly, PSs are biologically active molecules with multiple health applications, and increasing evidence has shown that PS activity depends on various criteria, such as formulation and solubility in the food matrix ( Schiepers et al, 2009 ; Poudel et al, 2019 ). Nonetheless, as humans cannot synthetize PSs, they should obtain them from diet ( Cabral and Klein, 2017 ).…”
Section: Introductionmentioning
confidence: 99%